Effect of parasitic plant Cuscuta australis R. Br. on growth of three invasive plants - YANG Bei-fen; LI Jun-min (浙江大学学报. 农业与生命科学版)
Effects of parasitic plant Cuscuta australis on the growth of three invasive plants, including Erigeron annuus, Chenopodium ambrosioides and Bidens pilosa, were investigated in a common garden experiment. The parasitic C. australis decreased significantly the root length of invasive E. annuus, but had no significant effect on that of invasive C. ambrosioides and B. pilosa. The parasitic C. australis decreased significantly the stem length and total length of three invasive plant species, in which the stem length and total length of E. annuus reduced up to 67.4% and 63.4%, respectively. The parasitic C. australis decreased significantly the root, leaf, stem, above-ground and total biomass of three invasive plants, in which the root, stem and leaf biomass of E. annuus reduced up to 46.8%,81.7% and 65.2% respectively. The parasitic C. australis increased significantly the root / shoot ratio of three invasive plants.